Effects of customer self-audit on the quality of maternity care in Tabriz: A cluster-randomized controlled trial - Gholipour, Kamal (PLoS One, 2018)
OBJECTIVE: To study the effects of customer self-audit on the service quality (SQ) and customer quality (CQ) of maternity care. DESIGN: A community-based cluster-randomized controlled trial. SETTING: Twenty-one health centres and health posts in Tabriz, Iran. PARTICIPANTS: Of 21 health centres/health posts, 10 were randomly assigned to the intervention group and 11 randomly assigned to the control group. Participants were 185 pregnant women selected from health centre/post registration lists (intervention group: n = 92; control group: n = 93). INTERVENTIONS: The intervention was a customer self-audit based on the CenteringPregnancy(®) model of prenatal group care. The intervention group attended group support sessions focused on participants’ opinions, questions, and self-management concerns. They also received sessions on experiential learning, coping, problem-solving, and goal-setting by a family health expert, a midwife, and a doctor. Control group participants continued to receive individual care. PRIMARY OUTCOME MEASURES: SQ and CQ were assessed using questionnaires. Patients rated the importance and performance of non-health quality dimensions. SQ was calculated as: SQ = 10 − (Importance × Performance). RESULTS: Total mean SQ scores were 7.63 (0.91) and 8.91 (0.76) for the control and intervention groups, respectively, a statistically significant difference (p<0.001). Compared with the control group, the intervention group scored higher on the SQ aspects confidentiality, communication, autonomy, availability of support group, dignity, safety, prevention, and accessibility. Total mean CQ scores for the control and intervention groups were 82.63(7.21) and 87.47 (6.75), respectively, a statistically significant difference (p<0.001). After intervention, 82.6% of intervention group participants and 50.5% of control group participants reached the highest stage of self-management, showing an ability to take care of themselves under stress and financial constraints. CONCLUSIONS: The group prenatal care customer self-audit improved the SQ and CQ of maternity care by increased involvement of participants and giving them active roles in the care process.